Conventional sintered Cu2-xSe thermoelectric material - Zhiming Geng; Dongliang Shi; Lu Shi; Ying Li; G. Jeffrey Snyder; Kwok-ho Lam (Journal of Materiomics, 2019)
As the featured material of the superionic thermoelectric (TE) material family, copper-chalcogenide Cu2-xSe is attracting growing research interest for its excellent TE performance derived from the satisfactory power factor and the ultra-low thermal conductivity induced by the superionic effect. Various efforts have been made and proved to be effective to further enhance the TE performance for Cu2-xSe. However, this material is still far from the application stage, which is mainly due to concerns regarding control of the properties and the costly complex fabrication technology. Here we report a scalable pathway to achieve high-performance and tunable Cu2-xSe, utilizing conventional sintering technology and copper (Cu)-vacancy engineering with an effective mass model. The figure of merit zT is a competitive value of 1.0 at 800 K for the optimized binary Cu2-xSe, based on the precise modeling prediction and Cu-vacancy engineering. The changes in TE properties of Cu2-xSe under heating-cooling cycle tests are also revealed. Our work offers the referable method along with the decent parent material for further enhancement of TE performance, paving a possible route for the application and industrialization of Cu2-xSe TE materials. Keywords: Thermoelectric, Copper selenide, Copper-vacancy engineering, Effective mass model